Overview of Approaches to Incorporate Dynamics into the Measurement of Complex Phenomena with the Use of Composite Indices - Anna Łatuszyńskam (Contemporary Economics, 2012)
Composite indices have substantially gained in popularity in recent years. Despite their alleged disadvantages, they appear to be very useful in measuring the level of certain phenomena that are too complex to express with a single indicator. Most rankings based on composite indicators are created at regular intervals, such as every month, every quarter or every year. A common approach is to base rankings solely on the most current values of single indicators, making no reference to previous results. The absence of dynamics from such measurements deprives studies of information on change in these phenomena and may limit the stability of classifications.This article presents the possibility of creating reliable, dynamic rankings of measured items and measuring the complex phenomena with the use of composite indices. Potential solutions are presented on the basis of a review of the international literature. Some advantages and disadvantages of the presented solutions are described and an example of a new approach is shown.
Keywords: C1; O1; 330; composite index; complex phenomena; dynamics